Current Situation, Problems, and Countermeasures of Modern Marine Ranch Construction in Zhuhai City - WENG Zheng; WU Qitao; FANG Kai; HUANG Haoran; CHEN Cheng; LIANG Cuiping (Haiyang Kaifa yu guanli)
Modern marine ranching, as an ecosystem and sustainable development model that combines environmental protection, resource conservation, and sustainable fisheries output, has broad development prospects and important strategic significance. Zhuhai City has abundant marine resources, and the construction of modern marine ranching has unique advantages. This paper analyzes the current development status of modern marine ranching construction in Zhuhai City, explores existing problems, and proposes countermeasures and suggestions for the construction of modern marine ranching in Zhuhai City, including aquaculture processing, seedling cultivation, fishery port economic zone construction, industrial integration, seafood branding, fishery equipment and smart fisheries, financial insurance and policy guarantees, talent introduction and cultivation, and recreational fisheries, providing reference opinions for the high-quality development of modern marine ranching in Zhuhai City.